Towards synthesis of application-specific forward error correction (FEC) codes - McClurg, Jedidiah, author; Baker, Lauren Zoe, author; Canizales, Ronaldo, author; Karki, Dilochan, author; ACM, publisher (Colorado State University. Libraries, 2024)
Forward error correction (FEC) is a key component of modern high-bandwidth networks. Typically implemented at the physical layer, FEC attaches error-correcting codes to blocks of transmitted data, allowing some corrupted blocks to be repaired without retransmission. We outline a synthesis-based approach for automatic exploration of the FEC-code design space, focusing on Hamming codes. We formally verify the correctness of a Hamming (128, 120) code used for FEC in the recent 802.3df Ethernet standard, and provide preliminary evidence that our prototype synthesizer can leverage user-provided formal properties to generate FEC codes that are highly robust, efficiently implementable, and tuned to support specific data formats such as IEEE floating points.
Keywords: forward error correction; program synthesis